Factors influencing the food consumption at modern restaurants in vavuniya: An application of ordered probit regression analysis - Thayaparan, A. (University of Jaffna, 2010)
Nowadays due to the changes in life styles, education, income, and consumption patterns, most of the people prefer to consume their food products from modern restaurants. Modern restaurants are characterized by food which is supplied quickly after ordering with minimal services and eating out gives consumers to satisfy their hunger, and need for convenience, pleasure, entertainment, time saving, social interaction and the mood transformation. The objective of this study is to examine the relationship between consumers’ food away from home consumption frequency and their socio-economic/ demographic characteristics and attitudes at modern restaurants in Vavuniya. The food product consumption from modern restaurants has been gradually grown after 2000 and there are now more than seven restaurants in Vavuniya. Seven restaurants were surveyed in 2009 and it has been done among the households in both city and rural areas. Primary data were collected from a total of 245 respondents through a structured questionnaire and judgment sampling techniques were used. For the above purpose, the estimation techniques such as descriptive statistics, ordered probit model and marginal effects were analysed. The descriptive analysis of the data revealed the food consumption patterns of the respondents and this results showed that, 2.8% of the respondents never consumed food, 60.7% of them consumed food on occasional basis, 17.9% consumed food once or twice a month and 18.6% of them consumed food once a week in the restaurants in Vavuniya. Further, an empirical model was estimated using an ordered probit approach to obtain the coefficients applied to the calculation of marginal effects and probabilities. The sign and significance of coefficients and marginal effects were used to ascertain consumer characteristics which are important to the frequency of food consumption at modern restaurants. The results from the ordered probit model indicate that age, status of employment, size of the households, education, income and other factors of the respondents, attitudes toward the price of the food products, convenience and health concerns significantly influence the frequency of food consumption. In particular, smaller households are more likely to consume food products than larger households. Overall, the results of the ordered probit model suggests that being in large household is the characteristic which has the highest negative effect on the frequency of food consumption while being in the household with one child with one child with higher education and income levels are the characteristics that contribute to the highest positive effect on the probability of consumption. The findings will help modern food managers to understand the critical factors that influence consumers’ food consumption behaviour and help them to make improvements accordingly